Structural features of the Mahishasuramardini Temple - Temples of India Project Team (Jio Institute, 2024)
The Mahishasuramardini Temple has a pitha (a small platform) and well-defined base mouldings, with a plain jangha (wall) adorned with only a decorative band at its upper part. The varandika (moulded parapet) supports the latina shikhara (mono-spired) with navabhumis (nine tiers). The shikhara (superstructure) is intricately carved with the jala of chaitya arches, and at its apex, it features amalasaraka a segmented or notched stone disk), chandrika (are a series of amalaka discs), another amalasaraka topped by a kalasha (pitcher shaped finial).